Pemanfaatan Content Management System (CMS) Berbasis PHP sebagai Media Digital Upaya Branding Pengenalan Diri (Personal) pada Koperasi Konsumen KPRI Pascapanen Bogor - Rahmat Tri Yunandar; Enok Tuti Alawiah; Dicky Haryanto; Helina Apriyani (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Community Service is one of the important points of the Tridharma of Higher Education. In essence, lecturers are facilitators who play an active role in activities that are beneficial to society. Currently partners only have a few computers and only a small number of staff are able to operate computers properly. The public will be able to get to know more closely the role and contribution of the KPRI Pascapanen Cooperative by opening a blog which contains personal branding and activities carried out by staff and members or administrators of the KPRI Pascapanen Bogor Cooperative. Community service activities with target partners, namely staff and members of the KPRI Pascapanen Cooperative, have been carried out by providing training on the use of a PHP-based Content Management System (CMS) as digital media for self-introduction (personal) branding efforts at the KPRI Pascapanen Cooperative. Activities were carried out offline in the KPRI Pascapanen Cooperative Secretariat Hall. The results of the activity show that partners' skills and abilities have increased in utilizing a PHP-based Content Management System (CMS) as digital media for self-introduction branding efforts for KPRI Pascapanen cooperative staff.